(untitled) (Research, Society and Development, 2022)
The steel industry is one of the most solid markets in Brazil, it is also responsible for a large economic contribution in the country. However, activities related to steel production have a direct impact on socio-environmental issues. In this way, it is essential to discuss the sustainability approach in this environment, since there is an urgency in this sector. Therefore, the general objective of this work is the elaboration of a bibliographic review on the steel industry in Brazil, relating the steel production chain, the production processes and sustainability in the middle of a review. The methodology used is based on a more qualitative approach, using Bardin’s content analysis as a resource to analyze works found through two descriptors: steel production chain and steel production. During the development of this content, it was found that the steel industry has a highly relevant role in the Brazilian scenario and that new and challenging initiatives are underway to make the steel industry compatible with acceptable environmental parameters, within a perspective of mitigating possible impacts, mainly regarding the control of greenhouse gas emissions. Finally, it is concluded that the objectives proposed in this work were achieved as the results reveal that the steel industry, aligned with the environmental perspectives of sustainability, has been gaining more relevance and insertion in the agendas of business ventures.